THE STUDENTS’s ABILITY IN STUDYING SPELLING - Muhammad Emil Hesky Siregar; Sifa Askya; Putri Rizki Utami Hasibuan; Yani Lubis (Jurnal Publikasi Manajemen Informatika, 2025)
The Indonesian language cannot be ignored. Correct spelling not only affects someone's first impression of our writing but can also influence the reader's understanding and interpretation of the content. Therefore, understanding and mastering Indonesian spelling well is very important. That focus on promoting cultural awareness and understanding within the team can help mitigate these challenges (Carla, 2001). There are several methods that can be implemented to improve students'' spelling skills. One effective approach is to incorporate regular spelling practice into the curriculum The paper emphasizes the importance of recognizing the diverse needs of students in writing instruction.